Pengaruh Keteladanan Guru terhadap Akhlak Peserta Didik Kelas VIII - Amir, Ahmadul Haady Ihsan; Hakim, Ahmad; Syahid, Akhmad; Bunyamin, Andi; Mustamin, Mustamin; Assaad, Andi Baso Muammar; Wahab, Abdul (Al Asma: Journal of Islamic Education, 2025)
Teacher role models are an important factor in shaping students' morals. This research is motivated by findings at MTs As'adiyah Putera Pusat Sengkang, which indicate that some students' moral development is not optimal, even though teachers have provided good examples. This study aims to analyze the influence of teacher role models indicators of fairness, patience, authority, and compassion on the morals of eighth-grade students. The approach used is quantitative, using an ex post facto design. Data were collected via questionnaires from 73 students randomly selected from a population of 265, and the data were analyzed using multiple linear regression after meeting the classical assumptions. The results showed that, to some extent, the four role-model indicators did not have a significant effect on students' morals. However, simultaneously all four had a significant effect with a contribution (R-Square) of 15.1%. This finding indicates that the formation of students' morals is not sufficient to highlight a single exemplary trait, but requires the synergy of multiple teacher characters. The implication of this research is the importance of strengthening teachers' personality competencies holistically in order to foster more optimal moral formation in the educational environment